Assessment of oxidative DNA damage, apoptosis and histopathological alterations on zebrafish exposed with green silver nanoparticle. Issue 7 (9th August 2022) - Kokturk, Mine; Yıldırım, Serkan; Atamanalp, Muhammed; Calimli, Mehmet Harbi; Nas, Mehmet Salih; Bolat, Ismail; Ozhan, Gunes; Alak, Gonca
ABSTRACT: The effect of green synthesis approaches in NP synthesis and their possible toxicity in aquatic environments has been very limitedly studied. In this study, VA-Ag / AC NPs were synthesised using Viscum album plant as a reducing agent and Chenopodium album (CA) plant as an active carbon source. TEM (Transmission Electron Microscope) and XRD (X-ray crystallography) analysis of the synthesised VA-Ag / AC NPs were performed to detect their morphological and chemical properties. The inducing of oxidative stress and the effectiveness of VA-Ag/AC NPs in neurotoxic pathways and teratogenic changes in aquatic organisms have been investigated. In addition, a modelling was created to elucidate the toxicity mechanism. The results revealed that green synthesised VA-Ag/AC NPs nanoparticles are approximately 1600 times less toxic than nanoparticles synthesised by different methods. It had been determined that only high doses of VA-Ag/AC NPs nanoparticles cause neurological, histopathological and morphological changes. The findings in this study for VA-Ag/AC NPs, which are the evidence of the complexity of their mode of action at the cellular level, are a first in the aquatic ecosystem and require different findings regarding the stability and safety of such synthesis products.